Does FinTech Adoption Enhance MSME Performance? The Role of Financial Behaviour and Digital Financial Literacy - Nani Rohaeni; Meutia Meutia; Ina Indriana; Yeni Januarsi (Shirkah: Journal of Economics and Business, 2026)
Despite their vital contribution to Indonesia’s regional economy, MSMEs continue to face challenges related to limited financial literacy and low FinTech adoption, which constrain financial behaviour and business performance in the digital era. This study examines the effects of digital financial literacy and FinTech adoption on MSME financial performance, with financial behaviour serving as a mediating variable. A quantitative explanatory design was employed using survey data from 150 MSME owners in Banten Province, Indonesia. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to examine both direct and indirect relationships among the constructs. The findings reveal that financial literacy significantly influences financial behaviour (β = 0.151, p = 0.034) and exerts the strongest direct effect on MSME financial performance (β = 0.483, p < 0.001). FinTech adoption significantly affects financial behaviour (β = 0.713, p < 0.001) and financial performance (β = 0.188, p = 0.024). Financial behaviour positively influences financial performance (β = 0.231, p = 0.016). Furthermore, financial behaviour significantly mediates the relationship between FinTech adoption and MSME financial performance (β = 0.165, p = 0.037), but does not significantly mediate the relationship between financial literacy and financial performance (β = 0.035, p = 0.195). This study contributes to the MSME digitalization literature by clarifying the distinct pathways through which financial literacy and FinTech adoption shape business performance through financial behaviour.